Integrated weed management programs at oil palm plantation -A Survey - Kamalul Adham, Che Ruzlan; Muhammad Saiful, Ahmad Hamdani (International Journal of Agriculture, Forestry and Plantation, 2021)
Weed control is always regarded as one of the essential operations in the oil palm plantation management. It is the second most costly operation after fertilising. Hence, it is vital to manage noxious weeds’ growth in oil palm plantation areas effectively. Integrated weed management (IWM) refers to a system of sustainable weed management. This system is comprehensive through various control strategies that are undeniably capable of reducing the weeds’ impact to reach economically acceptable levels. The most widely practiced IWM method by plantation companies has been mainly spraying herbicide and cultural practices; many companies are solely depending on the chemical approach for weed control. Our survey indicated that IWM methods always produced lower management costs than non-IWM in FGV Lepar Utara. This indicates that the implementation of IWM could save on weed control cost up to RM34.00/ha/year. Besides, the cultural practices like mulching (in immature palm) and EFB applications would reduce weeding cost-efficiently. In addition, the arrangement of fronds, circle raking would reduce weeding cost. Thus, the combination of chemical control and cultural practices was preferred. As a conclusion, it would be appropriate to argue that through IWM implementation, among others, weed populations will be reduced to manageable levels, in addition to the environmental impact that can be reduced significantly instead of adopting an individual weed management practice and reducing the occurrence of herbicide resistance in weed species.